Environmental Transformation with Social Value in the “La Primavera” Neighborhood of Sincelejo, Sucre, Colombia - González, Lewis Pereira; Molino, Mario Alfonso Gándara; Herrera, Jhon Anaya; Osorio, Pedro Martínez; Ruge, Cesar Duran; T., Alejandro Guerrero; Beltrán, Lilibeth de Aguas (Journal of Ecohumanism, 2025)
Objective: the article refers to the preliminary results of an intervention process carried out in a community in the north of the city of Sincelejo, capital of the Department of Sucre, Colombia, whose purpose was the construction of ecological citizenship and the establishment of organizational meta-contingencies that would improve the collective intelligence of the community, raising its self-management capacities. It was a university social responsibility program led by the Corporación Universitaria del Caribe CECAR, for the improvement of the integral management of solid waste and the cultural dynamics related to the coexistence present there. Methods: the methodology of knowledge production focused on the ethnographic systematization of community development experiences applied to the strategies of collective co-creation, urban intervention (construction of an ecopark) and cultural transformation. The process linked the work of an interdisciplinary team of researchers and students of architecture, social work, natural sciences, anthropology and economics, the community and some government and business entities. Results: the results suggest the possibility of establishing meta-contingencies of an organizational nature that initiate a process of transformation if the necessary care is taken in the constitution of the organizational instances of the communities, and that they, once constituted, can drive these transformations if they are constituted as authentic entities, that the change in social habits can be promoted from such instances, that in the process the mobilization of the inhabitants is possible with programs of “ecological art” and that the urban intervention can operate as a scenario of immersion that reinforces the change of collective attitude.